2017
DOI: 10.5606/ehc.2017.53247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proximal femoral nail-antirotation and cemented, bipolar hemiarthroplasty with calcar replacement in treatment of intertrochanteric femoral fractures in terms of mortality and morbidity ratios

Abstract: ÖZAmaç: Bu çalışmada proksimal femoral çivi-antirotasyon (PFNA) veya çimentolu, kalkar destekli, bipolar hemiartroplasti uygulanan intertrokanterik femur kırıklı hastaların mortalite ve morbidite oranları değerlendirildi. Hastalar ve yöntemler: Proksimal femur kırığı nedeniyle Ocak 2008 -Ocak 2011 tarihleri arasında tedavi gören 127 hasta (42 erkek, 85 kadın; ort. yaş 79.2 yıl; dağılım 55-98 yıl) ameliyat sırasında mortalite, toplam mortalite ve mortalite oranlarının aylara göre dağılımı açısından retrospektif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
4
27
0
Order By: Relevance
“…The goals of treatment of ITFs in the elderly are to regain preoperative ambulatory status with the lowest rate of medical and surgical complications 16 . Similar with published data 14 , in this study, we also find that PFNA and BPH have similar functional outcome, which means in the term of functional recovery, either PFNA or BPH is accepted for elderly ITFs patients. Consistent with previous results 17,18 , we also found that PFNA has shorter duration of operation time and less blood loss during surgery than BPH, which implies that PFNA does less surgical injury to patients.…”
Section: Acute Cerebral Infarctionsupporting
confidence: 92%
See 1 more Smart Citation
“…The goals of treatment of ITFs in the elderly are to regain preoperative ambulatory status with the lowest rate of medical and surgical complications 16 . Similar with published data 14 , in this study, we also find that PFNA and BPH have similar functional outcome, which means in the term of functional recovery, either PFNA or BPH is accepted for elderly ITFs patients. Consistent with previous results 17,18 , we also found that PFNA has shorter duration of operation time and less blood loss during surgery than BPH, which implies that PFNA does less surgical injury to patients.…”
Section: Acute Cerebral Infarctionsupporting
confidence: 92%
“…Cholangitis 1 www.nature.com/scientificreports www.nature.com/scientificreports/ patients 14,15 . However, it is still unclear whether BPH or PFNA is the better choice for elderly ITFs patients.…”
Section: Acute Cerebral Infarctionmentioning
confidence: 99%
“…Harris hip scores were 83 and 80.2 in PFNA and hemiarthroplasty groups, respectively, with no statistically significant difference between the groups. In contrary to other studies, a study by Esen E et al [14] showed that the Harris hip score were 78.34 and 82.8 in BPA and PFN groups respectively. The results of our study showed that both BPA and PFN are good treatment methods with better post operative outcomes in case of BPA which was also reported in a study by Sancheti et al [15] .…”
Section: Discussionmentioning
confidence: 62%
“…[ 9 11 ] Unfortunately, papers also show that BPH takes longer operation time and much more blood loss than PFNA, and recommend that BPH should be undertaken with caution in carefully selected patients. [ 12 15 ] So, until now, there is still no consensus whether BPH should be selected as the primary treatment for elderly patients especially patients aged 85 years or more presented with ITFs. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%